Alexandrium catenella resting cyst distribution in the Alaskan Arctic (2018-2019) - Evangeline Fachon; Donald Anderson (Arctic Data Center, 2021)
During a time of unprecedented ecological change in the Arctic, harmful algal blooms have become an issue of increasing concern. Alexandrium catenella is a dinoflagellate phytoplankton species which produces toxins known to cause paralytic shellfish poisoning (PSP), inducing sickness in people and marine animals that consume contaminated fish or shellfish. This species is found globally, but its extent in Arctic waters is still being described. While blooms generally occur in the upper water column, the life cycle of Alexandrium also includes a resting benthic stage known as a cyst; the distribution of these resting cysts can be used to understand bloom dynamics and even predict future bloom scenarios. This dataset (Alexandrium_AlaskanArctic_Cysts_2018_2019.csv) includes measurements of Alexandrium catenella resting cyst abundance in sediments collected during shipboard surveys in the Northern Bering Sea, Chukchi Sea, and Beaufort Shelf in 2018 and 2019 (see methods section for survey details). Additional species quantities are included at a subset of stations.